Experiencing diversity in a ODL higher education context - Moreira, Darlinda (2014)
Complex and global changes in societies have intensify migratory movements. Consequently, todays population in higher education institutions is characterized by a multidimensional diversity in terms of culture, life experience and expectations, that open up new intercultural universes of communication and learning. As a contribute to respond to this challenge, this paper presents results on the exploratory phase of the implementation of an online course focusing diversity in the population of higher education institutions in Europe. The course was designed, using a collaborative methodology approach, by a group of scholars, partners in the context of an European project. In order to engage students more deeply in learning and reflection, the pedagogical approach adopted was based in the development of interconnections between conceptual knowledge and digital storytelling pieces that were developed by students themselves under the teachers’ proposal and supervision.